First Fossil Record of Parasitic Flat-Bark Beetle (Coleoptera: Passandridae) from the Eocene of Patagonia, Argentina - Ramírez, Leonardo César (2015)
Catogenus punctatus sp. n. is the first fossil species described of the family Passandridae(Coleoptera: Cucujoidea) worldwide. The specimen was extracted from the Rio Pichileufú fossil-bearing strata, Huitrera Formation, Rio Negro, Argentina.